AHELO: The Myth of Measurement and Comparability - Altbach, Philip G. (International Higher Education, 2015)
AHELO, the OECD’s pilot programs to measure student achievement cross-nationally is about to be implemented internationally. This article argues that it is very difficult to measure learning cross-nationally—and recommends that AHELO be scrapped.